Determine the effect of storytelling in public libraries on the creativity of preschool children: An experimental research - nadjla hariri; yasaman pagardkar (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2016)
Purpose: The present study has been done to determine the impact of storytelling on creativity of children of 5 to 6 years old as the members of Imam Ali Public Library of Yazd city in Iran. Methodology: we used experimental research method with a pre-test and post-test plan as well as control group and a random selection. The research population included 60 members, 5-to-6 years’ old children who were the members of Imam Ali Public Library of Yazd city in Iran, in such a way that 30 children were randomly put in control group and 30 others in experimental group. The data were gathered through pictorial form B of Torrance test of creative thinking, and they were analyzed by one-way and two-way Covariance test. Findings: The mean value of creativity of experimental group who received storytelling variable was 34 percent more than the mean value of creativity among the control group. Therefore, storytelling effect on creativity of pre-elementary children was 0.34. Besides, the storytelling had a 21 percent positive effect on the initiative. Moreover, the expansion rate of the experimental group in post-test was 19 percent more than the pre-test. Likewise, we tested research hypothesis and the results showed that there was a significant relationship between storytelling and creativity growth for pre-elementary children, as storytelling raised initiative and boosted the expansion of ideas. Originality/Value: The value of this research circles around the demonstration of the effect of storytelling for children on their creativity and potentiality of imagination. One can infer from results that storytelling in pedagogical in informational foundations like public libraries should be emphasized.